A method for preparing a honeycomb alumina carrier

CN118108491BActive Publication Date: 2026-10-27DALIAN UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410157425.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-04
Publication Date
2026-10-27
Estimated Expiration
2044-02-04

AI Technical Summary

Technical Problem

但这种涂层的方法普遍存在涂层易脱落的缺陷,而且涂覆成本较高

Benefits of technology

[0024]本发明各物质相互配合使蜂窝状坯体无需密封老化,直接干燥不开裂,经焙烧获得蜂窝状氧化铝载体。所述的蜂窝状氧化铝载体以粒径较小的含铝化合物为无机主料,材料粒度小,致使颗粒间隙小,颗粒间接触点多,挤出成型后载体的轴向抗压强度大。并且添加助剂及胶溶剂用量少、对环境污染小、都可在焙烧中去除,载体不会在成型的过程中引入杂质。载体组成为单一的氧化铝,有较大的比表面积,介孔孔径较为集中,原料廉价易得,制备工艺简单,在制备催化剂的过程中避免了涂覆高比表面积涂层的步骤,节约成本,具有良好的工业化前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118108491B_ABST
    Figure CN118108491B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a honeycomb-shaped alumina carrier, which comprises the following steps: uniformly mixing aluminum compound powder and binder powder, and adding them into a kneader; uniformly mixing water, a peptizing agent and an extrusion aid, and adding them into the kneader, and then performing kneading to obtain a mud; the aluminum compound is aluminum hydroxide and / or pseudoboehmite; the mass of the water is 70-85% of the mass of the aluminum compound; the peptizing agent comprises one or both of nitric acid and acetic acid; the mass of the peptizing agent is 2-3.25% of the mass of the aluminum compound; the kneaded mud is taken out and aged; the honeycomb-shaped green body is obtained through extrusion molding; and the honeycomb-shaped green body is dried and calcined to obtain the honeycomb-shaped alumina carrier. The mutual cooperation of the various substances makes the honeycomb-shaped green body directly dried without cracking; the obtained honeycomb-shaped alumina carrier has high axial compressive strength, a large specific surface area, a relatively concentrated mesopore size, and the raw materials are cheap and easy to obtain, the preparation process is simple, cost is saved, and the honeycomb-shaped alumina carrier has a good industrialization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alumina preparation technology, and to a method for preparing a honeycomb alumina carrier, specifically a method for preparing a high specific surface area porous honeycomb alumina carrier. Background Technology

[0002] Powdered catalysts have problems such as high bed pressure drop and poor mass and heat transfer in industrial applications, which prevent them from being directly applied to industrial reactions. Therefore, it is necessary to process promising basic research catalysts into catalysts with certain shapes, high mechanical strength, and good pore structure.

[0003] Al2O3 has a wide range of applications, including catalysts and their supports, aluminum smelting, refractory materials, electronic packaging substrates, structural materials, and abrasives. Among these, the transition state γ-Al2O3 possesses many excellent characteristics, such as abundant pore structure, high specific surface area, and good adsorption properties, leading to its increasing use in petroleum, biochemical, and other industries. Currently, spherical alumina is the most commonly used in the market. Catalysts prepared using spherical alumina offer advantages such as uniform packing, uniform and stable fluid resistance, high bulk density, large loading and throughput, good wear resistance, and high adsorption or reaction efficiency. However, in practical applications, the gas resistance of spherical particle beds increases exponentially with increasing packing density. Therefore, high-power fans are required to allow gas to pass through the bed, increasing equipment energy consumption.

[0004] Honeycomb catalysts consist of numerous parallel and straight channels. Their high porosity and straight channel structure facilitate smoother fluid flow. Therefore, the catalysts not only exhibit low bed resistance and low pressure drop, but also high mass transfer efficiency, easy catalyst separation and regeneration, and minimal scale-up effects. Honeycomb ceramics serve as physical structural supports for hosting chemically active high specific surface area catalyst coatings. One representative coating is an alumina coating deposited on the walls of honeycomb ceramics. Patent CN103508755A discloses a method for coating alumina onto cordierite honeycomb ceramics, resulting in a uniform coating that is resistant to cracking and peeling. Patent CN103506099A discloses a method for preparing an alumina coating slurry on a honeycomb ceramic support. This method ensures good rheological properties of the alumina coating slurry, allowing for uniform coating onto the honeycomb ceramic support, and facilitates the removal of residual sol slurry. Patent CN101734946A improved the impregnation coating process by using a vacuum extraction impregnation method to uniformly coat alumina coating onto honeycomb ceramics, which was then used for toluene catalytic combustion purification. However, this coating method generally suffers from the defect that the coating is prone to peeling off, and the coating cost is relatively high.

[0005] Not all reactions are suitable for catalyst preparation using porous coatings. Some reactions are better suited to supporting the active components on a support made primarily or entirely of materials with high specific surface area. These reactions include chemical processes where diffusion and mass transfer steps occur more slowly in the catalyst's chemical reaction kinetics compared to the overall process. For example, the hydrodesulfurization of fossil fuels in the petrochemical industry to produce low-sulfur gasoline and diesel requires a support with a large specific surface area to more effectively utilize the reactor volume. This necessitates that the catalyst support be entirely made of materials with high specific surface area. Honeycomb structures with appropriate porosity and specific surface area are suitable for this application, offering high mass transfer efficiency, easy catalyst separation and regeneration, low pressure drop, less waste, and a more compact reactor structure.

[0006] Therefore, the preparation process of porous honeycomb alumina carriers with high porosity and high specific surface area needs further development. Summary of the Invention

[0007] The present invention relates to the preparation of a honeycomb alumina carrier with large specific surface area, high strength, and high porosity. Moreover, the process is simple, with low pollution and no introduction of impurities, and has certain industrialization prospects.

[0008] The technical solution of the present invention is as follows:

[0009] A method for preparing a honeycomb alumina carrier includes the following steps:

[0010] (1) The aluminum-containing compound powder and the binder powder are mixed evenly and denoted as powder A; water, adhesive solvent and extrusion aid are mixed evenly and denoted as solution B; powder A is added to a kneader, solution B is added to it, and the mixture is kneaded to obtain mud; the aluminum-containing compound is aluminum hydroxide and / or boehmite; the amount of water is 70-85% of the mass of the aluminum-containing compound; the adhesive solvent includes one or both of nitric acid and acetic acid; the amount of adhesive solvent is 2-3.25% of the mass of the aluminum-containing compound.

[0011] (2) Take out the kneaded clay and let it age;

[0012] (3) It is fed into a twin-screw extruder and extruded through a circular perforated plate;

[0013] (4) The extruded material is extruded and formed using a vertical extruder equipped with a honeycomb mold to obtain a honeycomb preform;

[0014] (5) The honeycomb preform is dried and calcined to obtain a honeycomb alumina carrier.

[0015] The adhesive solvent also includes citric acid, and the mass percentage of citric acid in the adhesive solvent is 1-50%.

[0016] The binder is one or more of methylcellulose, hydroxypropyl methylcellulose, guar gum powder and starch, and the amount of the binder is 3-10% by mass of the aluminum-containing compound.

[0017] The extrusion aid is one or more of glycerol, tartaric acid, polyethylene glycol and oxalic acid, and the amount of the extrusion aid is 1-2% of the mass of the aluminum-containing compound.

[0018] The aging time is 3-24 hours.

[0019] The drying process involves air-drying at room temperature followed by baking at 25-50℃ to maintain the parallel structure of the honeycomb channels and prevent cracking.

[0020] The calcination temperature is 600-1000℃, the calcination time is 2-4h, and the heating rate is 1-3℃ / min.

[0021] The prepared honeycomb alumina carrier has an axial compressive strength of 3-10 MPa and exhibits ordered axial channels; furthermore, the specific surface area of ​​the honeycomb alumina carrier is 250-350 g / m². 2 The pore volume is 0.5-0.7 cm. 3 / g.

[0022] The honeycomb alumina can be square, round, hexagonal, or triangular in shape.

[0023] The beneficial effects of this invention are as follows:

[0024] This invention utilizes a synergistic combination of substances to allow the honeycomb preform to dry directly without sealing or aging, preventing cracking, and then calcining to obtain a honeycomb alumina carrier. The honeycomb alumina carrier uses aluminum-containing compounds with small particle sizes as the main inorganic material. The small particle size results in small interparticle gaps and numerous contact points, leading to high axial compressive strength after extrusion molding. Furthermore, the amount of additives and adhesives used is small, causing minimal environmental pollution, and all can be removed during calcination, preventing the introduction of impurities into the carrier during molding. The carrier is composed of a single type of alumina, possessing a large specific surface area and relatively concentrated mesopore size. The raw materials are inexpensive and readily available, and the preparation process is simple. It avoids the step of coating with a high specific surface area coating during catalyst preparation, saving costs and demonstrating good industrialization prospects. Attached Figure Description

[0025] Figure 1 This is a photograph of the honeycomb alumina carrier used in Example 1.

[0026] Figure 2 This is the adsorption-desorption isotherm diagram of the honeycomb alumina carrier in Example 5.

[0027] Figure 3 This is a pore size distribution diagram of the honeycomb alumina carrier in Example 5. Detailed Implementation

[0028] In this invention, the axial compressive strength refers to the compressive strength of the honeycomb alumina perpendicular to the cross-section of the pores. All axial compressive strength values ​​are arithmetic averages calculated after sampling and testing.

[0029] To make the objectives and technical solutions of this invention clearer, the invention will be described in detail below with reference to some examples. The specific embodiments described herein are only used to explain the invention and are not intended to limit the invention.

[0030] Example 1

[0031] 200g of commercial pseudoboehmite and 10g of hydroxypropyl methylcellulose were mixed in a mixer for 1 minute. 160g of deionized water, 5g of acetic acid, and 3g of glycerol were added sequentially to a beaker and placed in an ultrasonic cleaner for 30 seconds to mix thoroughly. The mixed powder was then kneaded in a kneader to form the desired clay and aged for 6 hours. The aged clay was then placed in a twin-screw extruder and extruded through a circular perforated plate. The extruded clay was then extruded using a vertical extruder equipped with a 9*9 square honeycomb mold to obtain a honeycomb-shaped preform. The honeycomb-shaped preform was dried at room temperature for 3 days, then dried in a 50℃ oven for 4 hours, and finally calcined at 600℃ for 2 hours to obtain a honeycomb-shaped alumina carrier, denoted as A1. A photograph of the actual product is shown below. Figure 1 As shown in (A). The results of the measurements of the molded products are listed in Table 1.

[0032] Example 2

[0033] The honeycomb alumina carrier was prepared using the same method as in Example 1, except that 4.5 g of acetic acid was added in combination with 160 g of deionized water and 3 g of glycerol, denoted as A2. The results of the molded product measurements are listed in Table 1.

[0034] Example 3

[0035] The honeycomb alumina carrier was prepared using the same method as in Example 1, except that 4g of acetic acid was added and mixed with 160g of deionized water and 3g of glycerol, denoted as A3. The results of the molded product measurements are listed in Table 1.

[0036] Example 4

[0037] The honeycomb alumina carrier was prepared using the same method as in Example 1, except that 4.5 g of acetic acid, 2 g of citric acid, 160 g of deionized water, and 3 g of glycerol were added and mixed together, denoted as A4. The results of the molded product measurements are listed in Table 1.

[0038] Example 5

[0039] A honeycomb alumina carrier was prepared using the same method as in Example 1, except that 4g of acetic acid, 2g of citric acid, 160g of deionized water, and 3g of glycerol were added and mixed together, denoted as A5. The results of the molded product measurements are listed in Table 1, and its adsorption-desorption isotherms are shown below. Figure 2 As shown, this is a type IV curve, with an H2 type hysteresis loop; the aperture distribution curve is as follows. Figure 3 As shown, it has a mesoporous structure with relatively concentrated pore size.

[0040] Example 6

[0041] Honeycomb alumina carriers were prepared using the same method as in Example 1, except that a 4x4 square honeycomb mold, denoted as A6, was used. A photograph of the actual product is shown below. Figure 1 (B) shows the results of the molded product measurements, which are listed in Table 1.

[0042] Example 7

[0043] The honeycomb alumina carrier was prepared using the same method as in Example 1, except that 5g of nitric acid was added and mixed with 160g of deionized water and 3g of glycerol, and a 4*4 square honeycomb mold was used, denoted as A7. The results of the molded product measurements are listed in Table 1.

[0044] Example 8

[0045] The honeycomb alumina carrier was prepared using the same method as in Example 1, except that 150g of deionized water, 5g of acetic acid, and 3g of glycerol were added and mixed, and a 4*4 square honeycomb mold, denoted as A8, was used. The results of the molded product are listed in Table 1.

[0046] Comparative Example 1

[0047] The honeycomb alumina carrier was prepared using the same method as in Example 1, except that 5g of citric acid was added and mixed with 160g of deionized water and 3g of glycerol, and a 4*4 square honeycomb mold was used, denoted as B1. The results of the molded product are listed in Table 1.

[0048] Comparative Example 2

[0049] The honeycomb alumina carrier was prepared using the same method as in Example 1, except that the main powder composition was changed from 200g of boehmite to 100g of boehmite and 100g of activated alumina, and a 4*4 square honeycomb mold was used. After extrusion molding, the mixture was dried at room temperature for 3 days, dried in an oven at 50°C for 4 hours, and calcined at 600°C for 2 hours to obtain the honeycomb alumina carrier, denoted as B2. The results of the molded product are listed in Table 1.

[0050] Comparative Example 3

[0051] A honeycomb alumina carrier was prepared using the same method as in Example 1, except that 100g of deionized water was added and mixed with 5g of acetic acid and 3g of glycerol, and a 9*9 square honeycomb mold was used. In this case, a complete honeycomb alumina could not be obtained, and it was designated as B3.

[0052] Comparative Example 4

[0053] The honeycomb alumina carrier was prepared using the same method as in Example 1, except that 190g of deionized water was added and mixed with 5g of acetic acid and 3g of glycerol, and a 9*9 square honeycomb mold was used. In this case, a complete honeycomb alumina could not be obtained, and it was designated as B4.

[0054] Comparative Example 5

[0055] The honeycomb alumina carrier was prepared using the same method as in Example 1, except that 10g of acetic acid, 160g of deionized water, and 3g of glycerol were added and mixed. A 4*4 square honeycomb mold was used, but a complete honeycomb could not be obtained, which was designated as B5.

[0056] Table 1 shows the molding and testing results of honeycomb alumina in each embodiment and comparative embodiment.

[0057]

[0058] As can be seen from Examples 1-9, Comparative Examples 1-5, and the results in Table 1, the method of the present invention can produce honeycomb alumina carriers with high strength, large specific surface area, and relatively concentrated mesopore size while ensuring the yield rate.

[0059] The above description is only a few embodiments of the present invention and is not intended to limit the present invention. Any modifications, substitutions and alterations made in accordance with the claims of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a honeycomb alumina carrier, characterized in that: Includes the following steps: (1) The aluminum-containing compound powder and the binder powder are mixed evenly and denoted as powder A; the water, adhesive solvent and extrusion aid are mixed evenly and denoted as solution B; powder A is added to a kneader, solution B is added to it, and the mixture is kneaded to obtain mud; the aluminum-containing compound is boehmite; the amount of water is 70-85% of the mass of the aluminum-containing compound; the adhesive solvent includes one or both of nitric acid and acetic acid; the amount of adhesive solvent is 2-3.25% of the mass of the aluminum-containing compound. (2) Take out the kneaded clay and allow it to age; (3) It is placed in a twin-screw extruder and extruded through a circular perforated plate; (4) The extruded material is extruded and formed using a vertical extruder equipped with a honeycomb mold to obtain a honeycomb preform; (5) The honeycomb-shaped blank is dried and calcined to obtain a honeycomb-shaped alumina carrier; The binder is one or more of methylcellulose, hydroxypropyl methylcellulose, guar gum powder and starch, and the amount of the binder is 3-10% by mass of the aluminum-containing compound. The extrusion aid is one or more of glycerol, tartaric acid, polyethylene glycol and oxalic acid, and the amount of the extrusion aid is expressed as 1-2% by mass of the aluminum-containing compound.

2. The method for preparing a honeycomb alumina carrier as described in claim 1, characterized in that: The adhesive solvent also includes citric acid, and the mass percentage of citric acid in the adhesive solvent is 1-50%.

3. The method for preparing a honeycomb alumina carrier as described in claim 1, characterized in that: The aging time is 3-24 hours.

4. The method for preparing a honeycomb alumina carrier as described in claim 1, characterized in that: The drying process involves air drying in the shade followed by drying at 25-50°C.

5. The method for preparing a honeycomb alumina carrier as described in claim 1, characterized in that: The roasting temperature is 600-1000℃, and the roasting time is 2-4 h.

Citation Information

Patent Citations

  • Method for applying coating on cordierite honeycomb ceramics and applications thereof

    CN101734946A

  • Preparation method of alumina coating slurry on honeycomb ceramic carrier

    CN103506099A

  • Method for coating alumina coating on cordierite honeycomb ceramic

    CN103508755A

  • Preparation method of aluminum oxide carrier

    CN105983444A

  • Method for preparing alpha-Al2O3 carrier, and alpha-Al2O3 carrier obtained by method, and uses thereof

    CN109908882A